A Theological Analysis of Herman Bavinck's Two Essays on the Imitatio Christi between pietism and modernism - Bolt, John. (Lewiston : The Edwin Mellen Press, 2013)
This is an exploration into the mind of Herman Bavinck (1854-1921) whose name is still revered as one of the prominent leaders in the revival of Dutch Neo-Calvinism in the Netherlands that profoundly affected not only theology and the church but also education, politics and society more broadly. A new world of Bavinck thoughts have opened up with this first ever English translation of his two articles on the Imitation of Christ.
A THEOLOGICAL ANALYSIS OF HERMAN BAVINCK'S TWO ESSAYS ON THE IMITATIO CHRISTI: Between Pietism and Modernism; Copyright Page; Dedication; Table of Contents; Foreword; Preface; Chapter 1 -- Introduction; Chapter 2 -- The Imitation of Christ I; Chapter 3 -- The Intervening Years: Herman Bavinck as Neo-Calvinist Thinker; Chapter 4 -- The Bavinck System: A Trinitarian Cultural-Ethical Ideal; Chapter 5 -- The Imitation of Christ II (1918); Chapter 6 -- Conclusion: Bavinck, Kuyper, and The Imitation of Christ; A Concluding, Truly Scientific Postscript; Appendix A; Appendix B; Bibliography; Index.
Description based on print version record.
Keywords: Bavinck, Herman, -- 1854-1921 -- Criticism and interpretation; Jesus Christ -- Example; Bavinck, J.H. (Johan Herman), 1895-1964.; Creation; Grace (Theology); Missions -- Theory -- History -- 20th century; Missions -- Theory; Revelation; RELIGION / Christian Ministry / Missions; Electronic books